Dominance of open burning signatures in PM2.5 near coal plant should redefine pollutant priorities of India - Iravati Ray; Shoumick Mitra; Jariya Kayee; Shufang Yuan; S. M. Shiva Nagendra; Xianfeng Wang; Reshmi Das (npj Climate and Atmospheric Science)
Abstract India, heavily reliant on coal for power generation, has been a significant emitter of particulate matter (PM) bound lead (Pb) and other heavy metals. It is crucial to understand whether implementation of stricter norms in recent years have effectively reduced emissions from coal combustion. This study aims to investigate and quantify the primary sources of PM2.5 in an area housing a major lignite-fired power plant in South India using Pb isotopic compositions and elemental concentrations. Characteristic ratios such as V/Pb and Cu/Pb demonstrate negligible influence from coal combustion, and indicate that summer aerosols are influenced by open burning. In Pb triple-isotope space the PM2.5 aerosols plot away from coal, overlapping with open burning signatures. These indicate that the atmosphere is predominantly influenced by open burning of solid waste and biomass rather than coal combustion, suggesting a promising decrease in coal emissions. Bayesian mixing model demonstrates that solid waste & biomass burning is the largest anthropogenic contributor towards atmospheric Pb (up to 26%), even in a region of coal combustion and presence of medium and small-scale industries. The dominance of open burning as a pollution source in the vicinity of a lignite fired power plant highlights the necessity for better waste management strategies.